MECHANISMS OF CREATION AND FUNCTIONING OF CONTEXTUAL SYNONYMS IN NEWSPAPER TEXTS - Kazymir , Iryna; Yesypenko , Nadia; Mitrousova , Tetiana; Davydyuk , Yuliya; Beshlei , Olga (Bangladesh Journal of Multidisciplinary Scientific Research, 2026)
Newspaper discourse is characterized by high lexical variability aimed at ensuring semantic precision, stylistic diversity, and expressive evaluation of events. However, the mechanisms through which contextual synonyms are formed and function across different topical domains remain insufficiently systematized, particularly in quantitative and discourse-oriented terms. The study investigates the dominant mechanisms of creating contextual synonyms in English-language newspaper texts and examines their functional differentiation in medical, sports, and political discourse. The empirical basis of the research consists of 304 newspaper articles, including 197 medical, 66 sports, and 41 political texts, selected from British mass-market and quality newspapers published between 2021 and 2024. The study employs contextual analysis to establish synonymy within specific micro-contexts, lexico-stylistic analysis to classify the principal lexical and stylistic mechanisms involved in the creation of contextual synonymy, and statistical analysis to quantify their distribution, using semantic, functional, and referential criteria for identification. The results reveal clear domain-specific patterns in the distribution of mechanisms of contextual synonymy. In medical media texts, nominalization is the most frequent mechanism (18%), followed by metaphorisation (15%) and metaphtonymisation (7%), while pronominalisation (10%) and numeralisation (8%) serve to generalize and structure statistical information. In sports discourse, nominalization is likewise dominant (20.8%), accompanied by metaphorisation (8.3%) and periphrastic expressions (8.3%), reflecting the need for precise yet expressive event representation. Political texts demonstrate a predominance of periphrastic nominations for political figures (18%), with negative or neutral political action nominations (15%), geographical terms (15%), and military-situation nominations (13%) forming a substantial share of contextual synonym usage. The findings indicate that contextual synonymy in newspaper discourse is organized through stable semantic–functional–referential overlap and realized through quantitatively differentiated lexical-stylistic mechanisms, with nominalization prevailing in medical and sports discourse and periphrastic nomination predominating in political discourse.JEL Classification Codes: D83, L82, Z13, Z11.